1999
DOI: 10.1038/sj.ejcn.1600769
|View full text |Cite
|
Sign up to set email alerts
|

Waist circumference values in Spanish children—Gender related differences

Abstract: Objective: To obtain reference values of the waist circumference in Spanish children, and to investigate their dependence on age and gender. Design: Cross-sectional study. Setting: General school-age population. Subjects: A representative sample of the schools in Zaragoza, Spain, was drawn from seven schools. The population selected comprised 1728 children with ages ranging from 6.0±14.9 y. Of the original sample, 368 children (21.29%) were excluded because of chronic diseases or refusal. Finally, 1360 childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
102
2
9

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 18 publications
7
102
2
9
Order By: Relevance
“…In Spanish children (aged 6-14.5 years), hip measurements were greater than waist measurements in both sexes, and the two curves run nearly parallel in males. In females, while hip measurements grew continuously, waist measurements had the reverse tendency between the ages of 11.5 and 14.5 (Moreno et al, 1999). Our findings may contribute to the explanation of this fact: %TrFM is larger in males than in females, although the differences in our findings are only significant after the age of 16.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…In Spanish children (aged 6-14.5 years), hip measurements were greater than waist measurements in both sexes, and the two curves run nearly parallel in males. In females, while hip measurements grew continuously, waist measurements had the reverse tendency between the ages of 11.5 and 14.5 (Moreno et al, 1999). Our findings may contribute to the explanation of this fact: %TrFM is larger in males than in females, although the differences in our findings are only significant after the age of 16.…”
Section: Discussionmentioning
confidence: 43%
“…Studies of waist circumference in children from different countries agree that this variable increases with age for both boys and girls where boys have greater mean waist circumference values than girls at every age (Moreno et al, 1999;McCarty et al, 2001;Katzmarzyk, 2004;Wardle et al, 2006). The study in Spain showed that these differences were especially significant after the age of 11.5 years.…”
Section: Discussionmentioning
confidence: 85%
“…[18][19][20][21] Ethnic differences of WC have been described in adults 22,23 but have not been studied in children, although reference data for WC are available from a number of different countries. [24][25][26][27][28][29][30][31] Data for ethnic Chinese children have not previously been reported.…”
Section: Introductionmentioning
confidence: 99%
“…To date waist percentile curves have been developed for Italian, Cuban and Spanish children (Zannolli & Morgese, 1996;Martinez et al, 1994;Moreno et al, 1999). In this report we have presented the first working waist percentile curves for British children aged 5.0 -16.9 y, where we have been able to define the mean and distribution of waist circumference at each age.…”
Section: Discussionmentioning
confidence: 94%
“…Such evidence now suggests that obtaining information on waist circumference in children could be as useful as BMI as a means of identifying the overweight and obese in childhood population studies, and screening those children who could benefit from early dietary and exercise intervention. To these ends, waist circumference percentile curves have been generated for the Italian and Spanish childhood populations (Zannolli & Morgese, 1996;Moreno et al, 1999) but, as yet, no such data have been produced for the UK. We now present in this paper, the first set of working waist circumference percentiles obtained from data collected from British children.…”
Section: Introductionmentioning
confidence: 99%